Identification of Neisseria meningitidis nonlipopolysaccharide ligands for class A macrophage scavenger receptor by using a novel assay. - Peiser, L; Makepeace, K; Plüddemann, A; Savino, S; Wright, J; Pizza, M; Rappuoli, R; Moxon, E; Gordon, S (2006)
Macrophages (Mphi) may play an important role in the pathogenesis of invasive meningococcal infection. Previously, we have shown that the class A Mphi scavenger receptor (SR-A) is a major nonopsonic receptor for Neisseria meningitidis on Mphi. SR-A contributes to host defense by binding proinflammatory polyanionic ligands such as lipopolysaccharide (LPS) and by the uptake and killing of live organisms. SR-A-deficient mouse Mphi display a substantial reduction in the number of meningococci ingested compared to wild-type Mphi, and SR-A is required for meningococcal phagocytosis but not for the release of tumor necrosis factor alpha. Although soluble lipid A and lipid(IV)A are reported as ligands for SR-A, we demonstrated that LPS and LPS expression were not essential for the uptake of whole meningococci. In the present study, we set out to discover protein ligand(s) for SR-A in N. meningitidis lysates and outer membrane vesicles. Using various microbial mutant strains, we determined that molecules comprising the membrane capsule and pili, as well as the abundant surface Opa proteins were not essential for SR-A recognition. We developed a binding assay to detect SR-A ligands and identified three candidate proteins expressed on intact organisms, namely, NMB1220, NMB0278, and NMB0667. Soluble forms of these ligands were shown to block the binding of meningococci to CHO cells stably transfected with SR-A. Furthermore, NMB1220 was endocytosed by SR-A on Mphi and prevented internalization of soluble acetylated low-density lipoprotein. Thus, we have identified novel, unmodified protein ligands for SR-A that are able to inhibit meningococcal interactions with macrophages in vitro.